2012
DOI: 10.1097/ico.0b013e318223988e
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Segment Optical Coherence Tomography Features of Acute Corneal Hydrops

Abstract: Eyes with deeper DM detachments and larger DM breaks required more time for resolution of corneal edema despite intracameral C(3)F(8). This association needs to be validated by a prospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
0
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 17 publications
6
55
0
9
Order By: Relevance
“…A recent study has described three patterns of Descemet membrane detachment: detachment with break and rolled ends, detachment with break and flat ends, and detachment with no break [25]. Eyes with deeper Descemet membrane detachments and larger Descemet membrane breaks require more time for resolution of corneal edema despite intracameral gas injection [25]. Aurich et al [27] demonstrated that in intrastromal cysts, there is an area of hyporeflectivity within the corneal stromal bed on slit lamp adapted optical coherence tomography.…”
Section: Anterior Segment Optical Coherence Tomographymentioning
confidence: 97%
See 2 more Smart Citations
“…A recent study has described three patterns of Descemet membrane detachment: detachment with break and rolled ends, detachment with break and flat ends, and detachment with no break [25]. Eyes with deeper Descemet membrane detachments and larger Descemet membrane breaks require more time for resolution of corneal edema despite intracameral gas injection [25]. Aurich et al [27] demonstrated that in intrastromal cysts, there is an area of hyporeflectivity within the corneal stromal bed on slit lamp adapted optical coherence tomography.…”
Section: Anterior Segment Optical Coherence Tomographymentioning
confidence: 97%
“…2 a and b). A recent study has described three patterns of Descemet membrane detachment: detachment with break and rolled ends, detachment with break and flat ends, and detachment with no break [25]. Eyes with deeper Descemet membrane detachments and larger Descemet membrane breaks require more time for resolution of corneal edema despite intracameral gas injection [25].…”
Section: Anterior Segment Optical Coherence Tomographymentioning
confidence: 98%
See 1 more Smart Citation
“…A study of anterior segment optical coherence tomography of cases involving acute hydrops described two stages in resolution. 24 The first was reattachment of Descemet's membrane, followed by endothelial migration across the tear. There are no other associated ocular abnormalities with keratoglobus.…”
Section: Aetiological Factorsmentioning
confidence: 99%
“…Depuis les premières images du segment antérieur réalisées au milieu des années 1990, l'OCT-SA s'est rapidement développé avec de très nombreuses applications dans les pathologies du segment antérieur [17,18]. Des images de kératocône aigu ont été récemment décrites en IVCM ainsi que sur des coupes sagittales en OCT-SA [19][20][21]. Ces dernières ont permis de montrer que la taille de la brèche de la membrane de Descemet était corrélée à la durée de résorption de l'oedème cornéen et de suivre les différentes étapes de sa cicatrisation.…”
Section: Discussionunclassified